2008
DOI: 10.1139/b08-080
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-specific density affects plant growth responses to arbuscular mycorrhizas

Abstract: Arbuscular mycorrhizas can alter competitive interactions between plants that markedly differ in their dependence upon mycorrhizas, but little is known about how mycorrhizas affect intra- and inter-specific competition between similarly dependent plant species. We conducted competition experiments in pots between all pairs of the similarly facultatively mycotrophic crop species, chili ( Capsicum annuum L.), maize ( Zea mays L.), and zucchini ( Cucurbita pepo L.). We used a two-species yield-density model to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
1
12
0
3
Order By: Relevance
“…Negative effects on tomato root or shoot weights due to AMF could not be observed in the present work. However, lowest density here was two and not three plants, as in the work of Schroeder-Moreno and Janos (2008). With regards to interspecific competition, van der Heijden et al (2003) clearly showed that the AMF species can influence the outcome of a competitive situation between plants.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Negative effects on tomato root or shoot weights due to AMF could not be observed in the present work. However, lowest density here was two and not three plants, as in the work of Schroeder-Moreno and Janos (2008). With regards to interspecific competition, van der Heijden et al (2003) clearly showed that the AMF species can influence the outcome of a competitive situation between plants.…”
Section: Discussionsupporting
confidence: 60%
“…In return, however, arbuscular mycorrhizal (AM) fungal community structure can be influenced by the host plants (Smith and Read 2008; Bever 2002). These effects are well described for grassland communities; for crop species, only Schroeder-Moreno and Janos (2008) have reported similar effects. For the application of intercropping in combination with AMF, these feedback matters need to be kept in mind and need to be tested for each intercropping arrangement separately.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Studies investigating whether AMF can alter competitive interactions have mainly concentrated on comparisons of AMF taxa (Scheublin et al 2007) or the absence vs. presence of AMF inoculum on plant competition (Fitter 1977, Hartnett et al 1993, Hetrick et al 1994, Zobel and Moora 1995, Schroeder-Moreno and Janos 2008, Collins and Foster 2009. It is conceivable that the wide range of AMF-host-plant interactions may reduce the overlap of resource niches among coexisting plants, thus reducing interspecific competition and increasing complementarity between host plants and potentially increasing total plant community productivity.…”
Section: Introductionmentioning
confidence: 99%